2017
DOI: 10.7205/milmed-d-16-00079
|View full text |Cite
|
Sign up to set email alerts
|

Chondrotoxicity of Liposomal Bupivacaine in Articular Chondrocytes: Preliminary Findings

Abstract: Following 1 hour of treatment, liposomal bupivacaine demonstrated the highest chondrocyte viability. Chondrocyte viability was inversely proportional to anesthetic concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…By virtue of the formulation, this product has a longer duration of analgesic effect compared to bupivacaine HCl [15,19]. Although not currently approved for IA administration, a recent report describing the effects of liposomal bupivacaine on bovine and porcine chondrocyte viability, is encouraging with respect to the safety of this drug for IA use [16,17]. In the presently described study, we report on the plasma pharmacokinetics and synovial fluid concentrations of liposomal bupivacaine as well as chondrotoxicity following IA administration to horses.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…By virtue of the formulation, this product has a longer duration of analgesic effect compared to bupivacaine HCl [15,19]. Although not currently approved for IA administration, a recent report describing the effects of liposomal bupivacaine on bovine and porcine chondrocyte viability, is encouraging with respect to the safety of this drug for IA use [16,17]. In the presently described study, we report on the plasma pharmacokinetics and synovial fluid concentrations of liposomal bupivacaine as well as chondrotoxicity following IA administration to horses.…”
Section: Discussionmentioning
confidence: 97%
“…A secondary objective of this study was to assess the potential chondrotoxicity of liposomal bupivacaine following IA administration. Shaw and colleagues recently assessed the effects of liposomal bupivacaine on cell viability in cultured bovine chondrocytes. While decreased cell viability was noted in the chondrocytes incubated with bupivacaine HCl, no significant difference in cell count was found between cells treated with liposomal bupivacaine and 0.9% saline .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed chondrotoxicty at higher concentrations of 0.75% [19]. Shaw compared rovicapaine with liposomal bupivacaine, demonstrating higher viability of chondrocytes in the liposomal group [16].…”
Section: Discussionmentioning
confidence: 94%
“…A novel formulation of liposomal bupivacaine has recently been introduced, but there is a paucity of data published regarding the safety of intra-articular liposomal bupivacaine. Shaw et al harvested bovine knee cartilage and isolated the chondrocytes in the medium prior to exposure to liposomal bupivacaine, bupivacaine, and ropivacaine [16]. eir results showed that after a 1-hour exposure to liposomal bupivacaine, chondrocyte viability was similar to the control.…”
Section: Discussionmentioning
confidence: 99%